Development of an Interactive E-LKPD Based on Mathematical Literacy through Problem Based Learning Assisted by Wizer.me on Ratio - Aulia Nanda Tri Lestari; Vita Istihapsari (Journal of Educational Sciences, 2026)
The development of interactive electronic student worksheets (E-LKPD) that explicitly integrate mathematical literacy indicators into problem-based learning on ratio topics at the junior secondary level is still limited. This study aimed to develop an interactive E-LKPD based on mathematical literacy through problem-based learning (PBL) assisted by Wizer.me that meets validity and practicality criteria. The research employed a research and development method using the ADDIE model. The research subjects consisted of 29 seventh-grade students and one mathematics teacher, while validation was conducted by one content expert and one media expert. Data were collected quantitatively through expert validation sheets and teacher and student response questionnaires, and analyzed descriptively using percentage techniques. The results showed that the developed interactive E-LKPD was highly valid, with media expert validity of 80.2% and content expert validity of 86.4%, and practical based on teacher responses of 86.67% and student responses of 78.14%. These findings indicate that the interactive E-LKPD is suitable for use as a mathematics learning tool on ratio topics at the junior secondary level.